2015
DOI: 10.1075/lab.5.1.01cru
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual compound verbs in children’s Panjabi-English codeswitched narratives

Abstract: Bilingual compound verbs (BCVs) are documented in various languages and are common in codeswitching between English and South Asian languages. It has been suggested that BCVs have no monolingual equivalent, and are generated by a 'third system' independent of the two languages. BCVs have also been cited as evidence of language convergence, and as a strategy employed by dominant bilinguals to circumvent lexical gaps in one language. BCVs were common in narratives from four to six-year-old Panjabi-English childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Three recent studies throw further light on these issues. In her analysis of oral narratives from Panjabi/English children (ages 4-6), Crutchley [58] found that BCVs were particularly attested among less proficient bilingual children (i.e., "beginner bilinguals") who produced switched utterances that were shorter and less grammatically complex. Thus, Panjabi/English children's use of BCVs were not associated with syntactic complexity or innovation at the utterance level.…”
mentioning
confidence: 99%
“…Three recent studies throw further light on these issues. In her analysis of oral narratives from Panjabi/English children (ages 4-6), Crutchley [58] found that BCVs were particularly attested among less proficient bilingual children (i.e., "beginner bilinguals") who produced switched utterances that were shorter and less grammatically complex. Thus, Panjabi/English children's use of BCVs were not associated with syntactic complexity or innovation at the utterance level.…”
mentioning
confidence: 99%
“…It must be highlighted that Wichmann and Wohlgemuth's [27] view that lower levels of bilingualism result in the use of mixed verbs are supported by child bilingual data but not post-adolescent and adult data. Crutchley's [54] recent analysis of narratives from 14 Panjabi/English bilingual children showed that mixed verbs were especially attested among 'beginner bilinguals' with limited bilingual competence. These beginner bilinguals generally produced utterances that were less grammatically complex than those attested among more proficient bilingual children who primarily produced monolingual Panjabi utterances and less mixed verbs.…”
Section: Bi/multilingual Proficiency and Morphosyntactic Innovationmentioning
confidence: 99%
“…These beginner bilinguals generally produced utterances that were less grammatically complex than those attested among more proficient bilingual children who primarily produced monolingual Panjabi utterances and less mixed verbs. In Crutchley's [54] (p. 20) view, the type of CS among beginner bilinguals "exploit[ed] the simplest structures on offer in both languages", but it was not associated with grammatical complexity and/or morphosyntactic innovation.…”
Section: Bi/multilingual Proficiency and Morphosyntactic Innovationmentioning
confidence: 99%